Implementation of Visionary Leadership in Improving the Quality of Education at Al-Wahdah Kindergarten in Bandung City - Novianti, Herlin; Nurdin, Diding; Affandi, Nurdin (Institut Agama Islam Negeri (IAIN) Curup, 2025)
The objective of this study is to examine the implementation of visionary leadership in enhancing the quality of education at Al-Wahdah Kindergarten in Bandung City. The present study employed a qualitative approach with a case study method to collect data. In-depth interviews, participatory observation, and document analysis were used to gather information. The collected data were then analyzed using ATLAS.ti software. The findings indicate that the principal plays a pivotal role in establishing direction, facilitating change, serving as a spokesperson, and providing coaching. The principal's actions demonstrate strategic steps such as participative vision formulation, innovation in learning processes, effective communication, and systematic human resource development. A strong participatory vision, teacher commitment, and active parental involvement are all factors that lend support to the concept. Conversely, regulatory changes, resource limitations, and varying levels of adaptability among teachers act as inhibitors. The findings underscore the pivotal role of visionary leadership in enabling educational institutions to adapt and excel in challenging environments, thereby offering practical insights for principals and education policymakers.